A "sense of magnitude" requires a new alternative for learning numerical symbols. (2017) - Sasanguie, Delphine; Reynvoet, Bert
Abstract: Leibovich et al. proposed that the processing of numerosities is based primarily on a "sense of magnitude." The consequences of this proposal for how numerical symbols acquire their meaning are, however, neglected. We argue that symbols cannot be learned by associating them with a system that is not yet able to derive discrete numbers accurately because of immature cognitive control.